What is derivative of y = 1/(4e^(2x-1)+sin(e^(2x+1)))?

### 1 Answer | Add Yours

You need to differentiate the function using the quotient rule and the chain rule, such that:

`y' = (1'*(4e^(2x-1)+sin(e^(2x+1))) - 1*(4e^(2x-1)+sin(e^(2x+1)))')/((4e^(2x-1)+sin(e^(2x+1)))^2)`

`y' = (4*(e^(2x-1))' + (sin(e^(2x+1)))')/((4e^(2x-1)+sin(e^(2x+1)))^2)`

`y' = (4*2(e^(2x-1)) + 2e^(2x-1)*cos(e^(2x+1)))/((4e^(2x-1)+sin(e^(2x+1)))^2)`

`y' = (8(e^(2x-1)) + 2e^(2x-1)*cos(e^(2x+1)))/((4e^(2x-1)+sin(e^(2x+1)))^2)`

**Hence, evaluating the derivative of the given composed function, yields **`y' = (8(e^(2x-1)) + 2e^(2x-1)*cos(e^(2x+1)))/((4e^(2x-1)+sin(e^(2x+1)))^2).`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes